Probiotic drinks at home make your own seriously delicious gut-friendly drinks - Evans, Felicity (Sydney Murdoch Books, 2017)
Drawing from her personal experience as the owner of her fermented probiotic business Imbibe Living, Probiotics at Home covers both 'fermenting using a culture' and 'wild fermentation', with foundation recipes ranging from water kefir, coconut water kefir, milk kefir, jun and kombucha to Beet kvass, Pineapple tepache, Ginger bug and Honey mead. These basic recipes are then used as a basis to create some delicious and flavoursome elixirs, like Lemon and ginger kefir, Honey and vanilla ambrosia milk kefir and Jun with raspberries to Beet kvass with blood orange, Fragrant honey mead with star anise and cinnamon and Mint pineapple tepache. Complete with step-by-step instructions.
Keywords: Probiotics; Beverages -- Therapeutic use